Wetland use by wintering geese in the Gulf Coast Plains and Rice Prairie region of Texas, USA - Anderson, J T; Muehl, G T; Tacha, T C deceased (Wildfowl, 1999)
We studied wetland habitat use by wintering geese in the Coastal Plains and Rice Prairie Regions of Texas during 1991-92 and 1992-93. White-fronted Geese were most abundant on lacustrine littoral aquatic-bed floating vascular (x=2.10/ha) and unconsolidated shore organic (x=1.55/ha) wetlands. White geese (Snow and Ross’) were most abundant on estuarine intertidal aquatic-bed algal (x=8.71/ha) wetlands. Canada Geese were most abundant on lacustrine littoral unconsolidated shore vegetated (x=1.81/ha) wetlands. Geese used 16 of the 82 wetland types in the study area. Management of both open-water and vegetated wetlands is necessary to effectively influence the distribution and abundance of wintering geese.